Fournier's gangrene as a rare complication in patient with uncontrolled type 2 diabetes treated with surgical debridement: A case report and literature review. (February 2021) - Provenzano, D.; Lo Bianco, S.; Zanghì, M.; Campione, A.; Vecchio, R.; Zanghì, G.
Highlights: Fournier's gangrene (FG) is a rare disease which usually affects men. It is characterized by progressive necrotizing fasciitis. A 66-year-old man with uncontrolled type 2 diabetes, obesity with BMI 38, chronic kidney failure and chronic heart failure, reported the onset of symptoms about 14 days before his hospitalization, without consulting any doctor due to Covid-19 pandemic. The combination therapy of surgical debridement and antibiotics infusion was effective. Abstract: Introduction: Fournier's gangrene is a potentially fatal emergency condition, supported by an infection of perineal and perianal region, characterized by necrotizing fasciitis with a rapid spread to fascial planes. FG, usually due to compromised host, may be sustained by many microbial pathogens. Case report: A 66-year-old man, with a history of uncontrolled type 2 diabetes, obesity with BMI 38, chronic kidney failure and chronic heart failure, was admitted to the Emergency Department with a large area of necrosis involving the perineal and perianal regions. Discussion: Fournier's gangrene is favoured by hypertension, obesity, chronic alcoholism, renal and heart failure. Generally, Fournier's gangrene needs other procedures in addition to wound debridement such as colostomy, cystostomy, or orchiectomy. Conclusion: We report a case of FG found as complication in a patient with uncontrolled type 2 diabetes, treated with effective combination therapy with surgical debridement and antibiotics infusion.